Processing and Validation of Whey-Protein-Coated Films and Laminates at Semi-Industrial Scale as Novel Recyclable Food Packaging Materials with Excellent Barrier Properties - E. Bugnicourt; M. Schmid; O. Mc. Nerney; J. Wildner; L. Smykala; A. Lazzeri; P. Cinelli (Advances in Materials Science and Engineering)
A biopolymer coating for plastic films was formulated based on whey protein, and its potential to replace current synthetic oxygen barrier layers used in food packaging such as ethylene vinyl alcohol copolymers (EVOH) was tested. The whey-coating application was performed at semi-industrial scale. High barrier to oxygen with transmission rate down to ranges of 1 cm3 (STP) m−2 d−1 bar−1 at and 50% relative humidity (r.h.) but interesting humidity barrier down to ranges of 3 g m−2 d−1 (both normalized to 100 μm thickness) were reached, outperforming most existing biopolymers. Coated films were validated for storing various food products showing that the shelf life and sensory attributes were maintained similar to reference packaging films while complying with food safety regulations. The developed whey coating could be enzymatically removed within 2 hours and is therefore compatible with plastic recycling operations to allow multilayer films to become recyclable by separating the other combined layers. A life cycle assessment was performed showing a significant reduction in the environmental impact of the packaging thanks in particular to the possibility of recycling materials as opposed to incinerating those containing EVOH or polyamide (PA), but due to the use of biosourced raw materials.